MARC – introducing Malaysia digitally and globally / Sheela Paramasivam ... [et al.] - Paramasivam, Sheela; Adnan, Afni Anida; Luaran, PM Dr. Johan @ Eddy; Aisyah, Nur Fatima; Ganesan, Asha (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
Travel restrictions brought about by the Covid-19 pandemic have caused instructors worldwide to make changes from the traditional face-to-face method of teaching to online learning. This change not only affected the teaching and learning of content but also the running of other general programs such as orientation programmers for students in institutions of higher learning and universities who embark on their designated program of study. Between the months of February and June 2022, two staff of APB Seremban were given the opportunity to teach students from various universities situated in China, under the Global Studies Programme (GSC Global Short Course) run by UiTM’s Institute of Continuing Education and Professional Studies (ICEPS). These students were originally designated to study in Malaysia in a physical face-to-face mode before the Covid-19 pandemic. The syllabus of the study program included Malaysian Religion and Customs and the Zoom platform was used as the alternative teaching method.